Association between ALDH2 rs671 polymorphism and susceptibility to non-valvular atrial fibrillation in a Chinese population: a large-scale case–control study - Zhong, Fangming; Zhang, Qifeng; Ye, Zhuolian; He, Xuebo; Huang, Junping; Miao, Leiming (Frontiers in Physiology, 2026)
Non-valvular atrial fibrillation (NVAF) is the most common arrhythmia worldwide, with a steadily rising incidence and prevalence, posing a significant public health burden. Oxidative stress is recognized as a key driver of atrial remodeling and arrhythmogenesis. Mitochondrial aldehyde dehydrogenase 2 (ALDH2) plays a critical role in detoxifying reactive aldehydes, and the rs671 single-nucleotide polymorphism (G→A, Glu504Lys) markedly reduces enzymatic activity, with a high prevalence in East Asian populations. In this retrospective study, we analyzed 403 NVAF patients and 14,326 hospitalized controls from Meizhou People’s Hospital (2016–2020), aged ≥30 years (1:35.5 ratio), and constructed multiple propensity score-matched cohorts (1:15 to 1:2) to examine the association between ALDH2 rs671 and NVAF. The A allele frequency was significantly higher in NVAF patients than in the controls (32.0% vs. 24.2%, P < 0.001), causing an increased NVAF risk (OR = 1.472, 95% CI: 1.266–1.711). Multivariate logistic regression identified the GA genotype (OR = 1.681, 95% CI: 1.360–2.078, P < 0.001) and the AA genotype (OR = 1.558, 95% CI: 1.058–2.296, P = 0.025) as independent risk factors. Sensitivity analyses across various matching ratios confirmed the robustness of the association. Other independent risk factors included male sex, advanced age, hypertension, diabetes, coronary heart disease, and COPD.